PLAN DE MARKETING PARA LA EMPRESA PLOTTER. DE LA CIUDAD DE LOJA, PROVINCIA DE LOJA PERÍODO 2014 - Ortíz criollo, Andrea del Rocio (2015)
Plotter is a sole proprietorship, among its general functions is the provision of services in terms of printing and design plans, design models, counseling and 3D perspectives, has been operating three years in the lojano market and during this time has improved enhancing its technology services. PLOTTER during this short time has developed and implemented a marketing plan, which does not allow business development to increase sales, have a better position and market share, expand the customer base, look for different strategies to give alternative solutions to the problems that arise within the company and thus strengthen their image and quality of service. By the above, we feel the need for this research work, through the development and implementation of a marketing plan, whose overall objective is to develop a marketing plan for the company PLOTTER city of Loja; and two specific objectives: Perform an internal and external diagnosis of the company to investigate the current situation of the same. Make a proposal taking into account the needs and opportunities of it. To carry out the research work was taken into account such aspects as: Review of literature that refers to the design of a marketing plan. The methods used are the scientist who allowed all the theoretical basis of the investigation, the Deductive used in the overall analysis of the external environment to reach the particular analysis of internal analysis and propose marketing'plan. 6 The results of the external and internal analysis which identified different factors PESTC analysis, Portter five competitive forces, through the matrix EFE, EFI, SWOT and High Impact The action plan, which resides in the same four strategic objectives, which are: Develop a promotional plan offering added value services. Enabling it to attract new customers and counter the new competitors, whose value is 20.00 USD Make an advertising plan that allows the customer to know about the services offered by the company, worth $ 424.10 Expand and renovate the equipment to provide higher quality service, whose value is $ 1,749.00. Designing a training plan for human talent on issues related to the activities of the company, worth $ 480.00 The purpose of this plan and its implementation generally has a cos of $ 2,673.10. Also the main conclusions which states that the company provides a service to the timeliness and quality expected by customers regarding the development of different architectural designs are set, but not having a marketing plan has failed to take possession as must in the local market.